The Fabrication and Characterization of Piezoelectric PZT/PVDF Electrospun Nanofiber Composites. (11th March 2016) - Yun, Ji Sun; Park, Chun Kil; Jeong, Young Hun; Cho, Jeong Ho; Paik, Jong-Hoo; Yoon, Sun Hong; Hwang, Kyung-Ran
Piezoelectric nanofiber composites of polyvinylidene fluoride (PVDF) polymer and PZT (Pb(Zr0.53 Ti0.47 )O3 ) ceramics were fabricated by electrospinning. The microstructure of the PZT/PVDF electrospun nanofiber composites was characterized using X-ray diffraction (XRD), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The tensile properties (stress-strain curves) and electrical properties (P-E hysteresis loops) of the PZT/PVDF electrospun nanofiber composites were investigated as a function of PZT content from 0 wt% to 30 wt%. The results demonstrated that a PZT content of 20 wt% had enhanced tensile and piezoelectric characteristics.